The narrative identity of young adults with physical disability - Ryżanowska, Dorota (Disabled Student. Sketches and Theses, 2019)
The aim of the thesis was to explore the different ways of constructing the narrative identity by young adults with physical disability and to look for social and cultural factors which could have impact on the variety of constructions of respondents’ narrations about the one’s own life. The author used the Life Story Interview written by Dan Mc Adams. The examined persons were 40 young adults with different kind and moment of gaining disability. There were persons with motor and the visual disability in the researched group. The disability of answerers was natural or was a cosequence of the impairment of the body during one’s own life. The studies’ outcomes indicate that according to responders’ point of view the main impact on the process of forming their narrative identity have three groups of factors:1) the experiences connected with the social relationships, 2) the cultural factors, especially mass- media, 3) the experiences connected with one’s own body and its impairment. There were also exceptional factors in each individual story which significantly influenced the form of the person’s narrative identity. The analysis of the thematic literature [among others Edwards 2007, Leszczyńska 2010, Dunn, Burcaw 2016] shows that the results of this research may broaden the knowledge about factors which can be helpful in forming the narrative identity of young adults with physical disability.